Fe/Mn Oxide-modified Rice Straw Biochar for Cd Immobilization in Farmland Soil: Performance, Redox Potential Response, and Mechanism - Zhigen Li; Zhixin Liu; Chia Chay Tay; Fan Huang; Yuanzhao Cao; Baowei Hu (Water, Air, & Soil Pollution, 2026)

DNA barcoding reveals the species composition of chondrichthyan-based pet food products in the Taiwanese market - Yu-Chen Wei; Yu-Chun Wang; Ying-Xuan Li; Shih-Hui Liu; Chih-Wei Chang; Chia-Hao Chang (Conservation Genetics, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

Imiquimod-induced colitis: A novel ROS/ERK-driven model of intestinal inflammation and barrier dysfunction - Kuang-Ting Liu; Shu-Hao Chang; Kuan-Chen Wu; Zheng-Yi Li; Mao-Chia Chang; Yen-Chu Huang; Mu-Chi Chung; Shih-Chung Wang; Yi-Ju Chen; Jeng-Jer Shieh (Chemico-Biological Interactions, 2026)

Species delimitation within a taxonomically complex group: An example from the genus Apodemus (Rodentia: Muridae) - Xuan Pan; Buqing Peng; Xuming Wang; Zhongzheng Chen; Hao Cheng; Rui Liao; Chia-Lung Huang; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Stationary-Phase Antimicrobial Peptide Production in Escherichia coli - Wei-Sheng Yu; Ming-Hung Chen; Chia-Li Ting; Wen-Hsuan Tsung; Pei-Yu Sun; Po-Yu Liu; Si-Yu Li (Probiotics and Antimicrobial Proteins, 2026)

Urinary phthalate metabolites associate with blood levels of estrogen quinone-derived hemoglobin adducts in Taiwanese pregnant women - Shu-Li Wang; Dar-Ren Chen; Sheng-Yen Hsu; Chia-Wei Liu; Che Lin; Chien-Wen Sun; Pen-Hua Su; Ying-Chih Tseng; Po-Hsiung Lin (Toxicology Letters, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Salvianolic acid B protects against UVB-induced HaCaT cell senescence and skin aging through NRF2 activation and ROS scavenging - Jia-Ming Sun; Yu-Xin Liu; Yi-Tung Tsai; Yang-Dan Liu; Chia-Kang Ho; Dong-Sheng Wen; Ting-Yu Tsai; Dan-Ning Zheng; Ya Gao; Yi-Fan Zhang; Li Yu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Determination of 16 ultraviolet–absorbing compounds in marine invertebrates by using LC-USI-MS/MS coupled with QuEChERS - Yu-Fang Huang; Yan-Jun Liu; Kai-Chien Yang; Zi-Ying Li; Chia-Hsin Liu; Hsin-Chang Chen (Food Chemistry, 2024)

An Anisotropic Thermal–Mechanical Coupling Failure Criterion for Slate - Meng-Chia Weng; Shih-Shiang Lin; Chih-Shan Lee; Wei-Han Wu; Jia Han Li; Chih-Hsi Liu (Rock Mechanics and Rock Engineering, 2024)
This study investigates the thermal–mechanical behavior of slates in geothermal reservoirs and establishes an anisotropic thermal–mechanical coupling failure criterion. Slate samples obtained from a geothermal site were subjected to a series of direct-shear and triaxial-compression tests at various confining pressures and temperatures. The results showed that the orientation angle within a specific range caused shear sliding failure of the slate, primarily due to foliation strength; beyond this range, intrinsic rock properties led to different failure modes. Elevated temperatures significantly diminished the strength anisotropy of the slate. These findings provided a foundation for the development of an anisotropic thermal–mechanical coupling failure criterion. The validity of the proposed criterion, which incorporates both the orientation angle and thermal degradation effects, was demonstrated through experimental results. A three-dimensional surface diagram was constructed to visualize the relationship between the temperature, orientation angle, and failure principal stress, highlighting the anisotropic thermal-degradation characteristics of the slate under varying confining pressures. This study enhances the understanding of the thermal–mechanical behavior of these materials in geothermal reservoirs.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Overview of the population genetics and connectivity of sea turtles in the East Asia Region and their conservation implications - Connie Ka Yan Ng; Takashi Ishihara; Tomoko Hamabata; Hideaki Nishizawa; Min Liu; Jia-hao Song; Tsung Hsien Li; Chia-Ling Fong; Dae Yeon Moon; Il Hun Kim (Frontiers in Marine Science, 2024)
Understanding the current status and recent development of the population genetics and connectivity of sea turtles is crucial for effective conservation management of the species. Five sea turtle species, green turtle ( Chelonia mydas ), loggerhead turtle ( Caretta caretta ), hawksbill turtle ( Eretmochelys imbricata ), olive ridley turtle ( Lepidochelys olivacea ) and leatherback turtle ( Dermochelys coriacea ), are recorded in the East Asia Region situated in the western side of the North Pacific Ocean. We compiled information from 35 published genetic studies on the five sea turtle species, with a focus on green turtle and loggerhead turtle, which are the most studied species (in 30 studies) in view of their commonness and occurrence of nesting populations. We provided an overview of the key methods and findings of these previous studies, addressing two main objectives on genetic structure of the rookeries and their differences compared to other populations, and connectivity of the rookeries and foraging aggregations. By identifying information gaps and conservation needs, we discussed future developments for sea turtle genetic studies and conservation implications in the region.

Treating boron-containing wastewater by electrocoagulation-flotation (ECF) process with the stepwise addition of anionic surfactants - Yu-Jung Liu; Chia-Hui Yen; Yueh-Feng Li; Ching-Yao Hu (Journal of Water Process Engineering, 2024)

Boron removal from high sulfate-containing coal-fired power plant wastewater by an ultrasound/bipolar electrocoagulation process with aluminum electrodes - Yueh-Feng Li; Yu-Jung Liu; Chia-Hui Yen; Ching-Yao Hu (Journal of Environmental Chemical Engineering, 2023)

Environmental melamine exposure and adverse kidney outcomes in patients with type 2 diabetes mellitus - Yi-Chun Tsai; Chia-Fang Wu; Wei-Wen Hung; Ping-Shaou Yu; Chia-Chu Liu; Tusty-Jiuan Hsieh; Chu-Chih Chen; Sih-Syuan Li; Jia-Jen Chen; Yi-Wen Chiu; Shang-Jyh Hwang; Ming-Tsang Wu (Environmental Pollution, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

Suppression of Wnt/β-Catenin Signaling Is Associated with Downregulation of Wnt1, PORCN, and Rspo2 in Alzheimer’s Disease - Jesse R. Macyczko; Na Wang; Jing Zhao; Yingxue Ren; Wenyan Lu; Tadafumi C. Ikezu; Na Zhao; Chia-Chen Liu; Guojun Bu; Yonghe Li (Molecular Neurobiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Plastome phylogenomics of Allaeanthus, Broussonetia and Malaisia (Dorstenieae, Moraceae) and the origin of B. × kazinoki - Wen-Hsi Kuo; Shih-Hui Liu; Chiung-Chih Chang; Chia-Lun Hsieh; Yi-Hsuan Li; Takuro Ito; Hyosig Won; Goro Kokubugata; Kuo-Fang Chung (Journal of Plant Research, 2022)

Hypothermal Effects on Energy Supply for Ionocytes in Gills of Freshwater- and Seawater-Acclimated Milkfish, Chanos chanos - Chia-Hao Chang; Chia-Jui Liu; Wei-Jie Lu; Li-Yang Wu; Kuang-Jie Lai; Yu-Ting Lin; Tsung-Han Lee (Frontiers in Marine Science, 2022)
The milkfish, Chanos chanos , is an important aquaculture species that can be cultured in freshwater (FW) and seawater (SW) ponds because of its high euryhalinity. In winter, cold snap leading to high mortality of this tropical species is a critical issue for the aquaculture industry in Taiwan. Under hypothermal stress, however, changes in energy supply for osmoregulation of this euryhaline species is intriguing. In this study, we used an antibody against glycogen phosphorylase (GP) to identify glycogen-rich (GR) cells distributed adjacent to the mitochondria-rich (MR) ionocytes in milkfish gills. Glucose transporter 1 (GLUT1), which plays a major role in energy supply, was also identified and localized in GR cells. Moreover, the expression of indicators of aerobic metabolism and energy production, citrate synthase (CS) and cytochrome c oxidase (COX), were analyzed in gills of FW- and SW-acclimated milkfish to reveal different strategies of energy utilization under hypothermal stress. When exposed to a low-temperature environment, SW individuals used branchial glycogen and lactate to match the energy demands of aerobic metabolism in ionocytes, and elevated aerobic capacity to support and maintain normal functions in gills. However, branchial glycogen mainly localized in the GR cells of FW milkfish was not utilized under hypothermal stress. Meanwhile, a similar level of branchial COX activity and COXIV protein abundance at low temperatures between FW and SW milkfish indicated similar energy requirements in gills. This suggested that another source, but not branchial glycogen, maintained the energy demand in FW milkfish. The present study illustrated differential energy supply strategies in gills between SW- and FW-acclimated milkfish for osmoregulation under low temperatures.

Plastome phylogenomics of Allaeanthus, Broussonetia and Malaisia (Dorstenieae, Moraceae) and the origin of B. × kazinoki - Wen-Hsi Kuo; Shih-Hui Liu; Chiung-Chih Chang; Chia-Lun Hsieh; Yi-Hsuan Li; Takuro Ito; Hyosig Won; Goro Kokubugata; Kuo-Fang Chung (Journal of Plant Research, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Probabilistically quantifying the effect of geotechnical anisotropy on landslide susceptibility - Ya-Nan Ding; Dian-Qing Li; Chia Zarei; Bao-Long Yi; Yong Liu (Bulletin of Engineering Geology and the Environment, 2021)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Species diversity and molecular phylogeny of non-geniculate coralline algae (Corallinophycidae, Rhodophyta) from Taoyuan algal reefs in northern Taiwan, including Crustaphytum gen. nov. and three new species - Li-Chia Liu; Showe-Mei Lin; Annalisa Caragnano; Claude Payri (Journal of Applied Phycology, 2018)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Testing Darwin's transoceanic dispersal hypothesis for the inland nettle family (Urticaceae) - Zeng‐Yuan Wu; Jie Liu; Jim Provan; Hong Wang; Chia‐Jui Chen; Marc W. Cadotte; Ya‐Huang Luo; Bruno S. Amorim; De‐Zhu Li; Richard I. Milne (Ecology Letters, 2018)
Dispersal is a fundamental ecological process, yet demonstrating the occurrence and importance of long‐distance dispersal ( LDD ) remains difficult, having rarely been examined for widespread, non‐coastal plants. To address this issue, we integrated phylogenetic, molecular dating, biogeographical, ecological, seed biology and oceanographic data for the inland Urticaceae. We found that Urticaceae originated in Eurasia c . 69 Ma, followed by ≥ 92 LDD events between landmasses. Under experimental conditions, seeds of many Urticaceae floated for > 220 days, and remained viable after 10 months in seawater, long enough for most detected LDD events, according to oceanographic current modelling. Ecological traits analyses indicated that preferences for disturbed habitats might facilitate LDD . Nearly half of all LDD events involved dioecious taxa, so population establishment in dioecious Urticaceae requires multiple seeds, or occasional selfing. Our work shows that seawater LDD played an important role in shaping the geographical distributions of Urticaceae, providing empirical evidence for Darwin's transoceanic dispersal hypothesis.

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Optimization of the culture medium for recombinant protein production under the control of the αAmy3 promoter in a rice suspension-cultured cell expression system - Yu-Kuo Liu; Chia-Wei Lu; Jer-Yuan Chang; Ching-Fan Lu; Chia-Chun Tan; Li-Fen Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Assessment of germling ability of the introduced marine brown alga, Sargassum horneri, in Northern Taiwan - Showe-Mei Lin; Roger Huang; Hisao Ogawa; Li-Chia Liu; Yi-Chi Wang; Yushan Chiou (Journal of Applied Phycology, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Identification of low-molecular-weight vitellogenin 1 (Vg1)-like proteins as nucleotide excision repair (NER) factors in developing zebrafish (Danio rerio) using a transcription-based DNA repair assay - Yung-Chi Shen; Todd Hsu; Li-Bin Ling; Wen-Chian You; Chia-Wei Liu (Fish Physiology and Biochemistry, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

SMN is required for the maintenance of embryonic stem cells and neuronal differentiation in mice - Wei-Fang Chang; Jie Xu; Chia-Chun Chang; Shang-Hsun Yang; Hsin-Yang Li; Hsiu Mei Hsieh-Li; Mong-Hsun Tsai; Shinn-Chih Wu; Winston T. K. Cheng; Ji-Long Liu; Li-Ying Sung (Brain Structure and Function, 2015)

Phenotypic characterization of C57BL/6J mice carrying the Disc1 gene from the 129S6/SvEv strain - Liang-Wen Juan; Chun-Chieh Liao; Wen-Sung Lai; Chia-Yuan Chang; Ju-Chun Pei; Wan-Rong Wong; Chih-Min Liu; Hai-Gwo Hwu; Li-Jen Lee (Brain Structure and Function, 2014)

Ocular Delivery of pRNA Nanoparticles: Distribution and Clearance After Subconjunctival Injection - Liang Feng; S. Kevin Li; Hongshan Liu; Chia-Yang Liu; Kathleen LaSance; Farzin Haque; Dan Shu; Peixuan Guo (Pharmaceutical Research, 2014)

Discovery of indeno[1,2- $$c$$ c ]quinoline derivatives as dual topoisomerases I/II inhibitors: Part 3 - Chih-Hua Tseng; Cherng-Chyi Tzeng; Chiao-Li Yang; Pei-Jung Lu; Yu-Peng Liu; Hui-Ling Chen; Chien-Yu Chen; Chia-Ning Yang; Yeh-Long Chen (Molecular Diversity, 2013)

Inhibition of matrix metalloproteinase-9 expression by docosahexaenoic acid mediated by heme oxygenase 1 in 12-O-tetradecanoylphorbol-13-acetate-induced MCF-7 human breast cancer cells - Haw-Wen Chen; Che-Yi Chao; Li-Lin Lin; Chia-Yang Lu; Kai-Li Liu; Chong-Kuei Lii; Chien-Chun Li (Archives of Toxicology, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Polysaccharides purified from the submerged culture of Ganoderma formosanum stimulate macrophage activation and protect mice against Listeria monocytogenes infection - Cheng-Li Wang; Chia-Chen Pi; Chu-Wei Kuo; Yu-Jing Zhuang; Kay-Hooi Khoo; Wen-Hsiung Liu; Chun-Jen Chen (Biotechnology Letters, 2011)

An SSVEP-Actuated Brain Computer Interface Using Phase-Tagged Flickering Sequences: A Cursor System - Po-Lei Lee; Jyun-Jie Sie; Yu-Ju Liu; Chi-Hsun Wu; Ming-Huan Lee; Chih-Hung Shu; Po-Hung Li; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Changes in hydrogeological properties of the River Choushui alluvial fan aquifer due to the 1999 Chi-Chi earthquake, Taiwan - Cheng-Shin Jang; Chen-Wuing Liu; Yeeping Chia; Li-Hsin Cheng; You-Ching Chen (Hydrogeology Journal, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)

Urinary homovanillic acid (HVA) and vanillymandelic acid (VMA) in workers exposed to manganese dust - Ling Bao Ai; Lay Ha Chua; Ai Li New; Bee Lan Lee; Yi Mim Liu; Sin Eng Chia; Choon Nam Ong (Biological Trace Element Research, 1998)